2014
DOI: 10.1016/j.jacc.2014.03.031
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine-Mediated Effects of Ticagrelor

Abstract: This review constitutes a critical evaluation of recent publications that have described an additional mode of action of the P2Y12 receptor antagonist ticagrelor. The effect is mediated by inhibition of the adenosine transporter ENT1 (type 1 equilibrative nucleoside transporter), which provides protection for adenosine from intracellular metabolism, thus increasing its concentration and biological activity, particularly at sites of ischemia and tissue injury where it is formed. Understanding the mode of action… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
116
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 273 publications
(125 citation statements)
references
References 57 publications
1
116
0
Order By: Relevance
“…13,14 We have recently shown that 7-day oral pretreatment with ticagrelor, but not clopidogrel, limits myocardial infarct size (IS) in rats subjected to 30-minute coronary artery ligation followed by 24-hour reperfusion. 15 Importantly, the degree of platelet inhibition was comparable between the clopidogrel and ticagrelor arms indicating a P2Y 12 -and platelet-independent cardioprotective effect of ticagrelor. Indeed, the protective effect was mediated by adenosine receptor activation with downstream phosphorylation of protein kinase B (Akt), endothelial NO synthase, and activation of cyclooxygenase-2 (COX2).…”
mentioning
confidence: 93%
See 3 more Smart Citations
“…13,14 We have recently shown that 7-day oral pretreatment with ticagrelor, but not clopidogrel, limits myocardial infarct size (IS) in rats subjected to 30-minute coronary artery ligation followed by 24-hour reperfusion. 15 Importantly, the degree of platelet inhibition was comparable between the clopidogrel and ticagrelor arms indicating a P2Y 12 -and platelet-independent cardioprotective effect of ticagrelor. Indeed, the protective effect was mediated by adenosine receptor activation with downstream phosphorylation of protein kinase B (Akt), endothelial NO synthase, and activation of cyclooxygenase-2 (COX2).…”
mentioning
confidence: 93%
“…The effect should be sustained as long as sufficient ticagrelor exposure is present. [9][10][11][12] In a previous study we showed that 7-day pretreatment with ticagrelor upregulated COX2 expression and activity. 15 The protective effect of ticagrelor pretreatment was blocked with specific COX2 inhibitors, as well as aspirin.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…It is a direct-acting antagonist of P2Y 12 , which is a purinergic receptor for adenosine diphosphate (ADP) expressed by platelets. P2Y 12 plays an important role in thrombosis and homeostasis and defects in P2Y 12 to result in bleeding due to its role in ADP-induced platelet aggregation [4][5][6] . Due to these effects, ticagrelor is widely used to prevent stroke and acute coronary syndrome [7] .…”
Section: Introductionmentioning
confidence: 99%